PARADIGMA PENYELESAIAN SENGKETA BISNIS EKONOMI SYARI'AH MELALUI LEMBAGA LITIGASI DAN NON LITIGASI - Arif Hariyanto (LP2M Universitas Ibrahimy, 2013)
The Birth of Law No. 3 of 2006 Amendments Act No. 7 of 1989 On the Religious has brought major changes in the existence of the Religious institutions today.One fundamental change is the addition of the Religious authority agency (PA) in theeconomic field Shariah. Pursuant to Article 49 letter (i) of Act No. 3 of 2006 affirmed that the religious court has authority to examine, hear and resolve the case